2016
DOI: 10.1126/science.aah3374
|View full text |Cite
|
Sign up to set email alerts
|

Pathological α-synuclein transmission initiated by binding lymphocyte-activation gene 3

Abstract: INTRODUCTION Parkinson’s disease (PD) is the second most common neurodegenerative disorder that leads to slowness of movement, tremor, rigidity and in the later stages of PD, cognitive impairment. Pathologically PD is characterized by the accumulation of α-synuclein in Lewy bodies and neurites. There is degeneration of neurons throughout the nervous system with the degeneration of dopamine neurons in the substantia nigra pars compacta leading to the major symptoms of PD. RATIONALE In the brains of PD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
654
6
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 599 publications
(709 citation statements)
references
References 51 publications
22
654
6
8
Order By: Relevance
“…proteolytic degradation, endocytic escape, trafficking to recycling endosomes, etc.). The recent report of LAG3 as a putative receptor for ␣-syn uptake is compelling, although multiple receptors or transmission mechanisms for ␣-syn aggregate internalization are possible (58). For example, it has been demonstrated via flow cytometry that macropinocytotic uptake of both ␣-syn and Tau by immortalized cells and primary neurons is mediated by HSPGs (11).…”
Section: Discussionmentioning
confidence: 99%
“…proteolytic degradation, endocytic escape, trafficking to recycling endosomes, etc.). The recent report of LAG3 as a putative receptor for ␣-syn uptake is compelling, although multiple receptors or transmission mechanisms for ␣-syn aggregate internalization are possible (58). For example, it has been demonstrated via flow cytometry that macropinocytotic uptake of both ␣-syn and Tau by immortalized cells and primary neurons is mediated by HSPGs (11).…”
Section: Discussionmentioning
confidence: 99%
“…Lysosome dysfunction and oxidative stress can trigger the release of EVs containing aggregating α-synuclein, and those EVs can then be internalized and trigger the accumulation of toxic α-synuclein aggregates in previously healthy neurons (Emmanouilidou et al, 2010; Poehler et al, 2014; Zhang et al, 2018). Another potential mechanism for spreading of α-synuclein pathology is suggested by a study showing that misfolded preformed fibrils bind to LAG3 (lymphocyte-activation gene 3) and that LAG3 initiates α-synuclein preformed fibril endocytosis, transmission, and cytotoxicity (Mao et al, 2016). …”
Section: Perspective On How Mechanisms Of Aging Impact Neurological Dmentioning
confidence: 99%
“…In this regard, toll-like receptor 2 (TLR2) in neuron and microglial cells could serve as the receptor for extracellular αSYN oligomers (Kim et al 2013). Furthermore, a recent study has identified the lymphocyte-activation gene 3 (LAG3), also known as CD223, as the binding partner for preformed αSYN fibrils (Mao et al 2016). The LAG3 expressed on neurons may serve as a putative receptor for extracellular αSYN fibrils, leading to their endocytosis.…”
Section: How Does Exogenous α-Synuclein Get Into Cells?mentioning
confidence: 99%